Development Education and Education in International Development Policy: Raising Quality through Critical Pedagogy and Global Skills - Amy Skinner; Nicole Blum; Douglas Bourn (Revue Internationale de Politique de Développement)
Development education is an approach to learning that questions dominant paradigms of development and inspires citizen- and community-driven change towards a world of greater social justice. This article provides an overview of development education and reflects on the extent to which development education principles are currently reflected in, or missing from, mainstream educational policies pursued within an international development framework. In particular, the article addresses the issue of quality in education – one of the key current debates within international education policy – and suggests that, through its critical pedagogy and focus on the development of global skills, development education has a significant contribution to make to these debates. The article suggests that greater collaboration between the field of development education and international education policy could facilitate the creation of an agenda that focuses on education quality and learning processes, as opposed to the current preoccupation with education access and outcomes.